Trust and Trustworthy Computing c - Holz, Thorsten; Ioannidis, Sotiris; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 7th International Conference on Trust and Trustworthy Computing, TRUST 2014, held in Heraklion, Crete, Greece in June/July 2014. The 10 full papers and three short papers presented together with 9 poster abstracts were carefully reviewed and selected from 40 submissions. They are organized in topical sections such as TPM 2.0, trust in embedded and mobile systems; physical unclonable functions; trust in the web; trust and trustworthiness.
TPM 2.0 -- Trust in embedded and mobile systems -- Physical unclonable functions -- Trust in the web -- Trust and trustworthiness.
Keywords: Computer science; Computer security; Data encryption (Computer science).; Computers; Computers and civilization; Management information systems; Computer Science; Systems and Data Security; Management of Computing and Information Systems; Data Encryption; Computers and Society; Information Systems and Communication Service; Electronic books